STUDIES ON ANTIOXIDANT ACTIVITY OF SOME MEDICINAL PLANTS - VED PRAKASH; SHELLY RANA; ANAND SAGAR (International Journal of Pharma and Bio Sciences, 2016)
A large number of different biologically active and therapeutic potential phytochemicals are drawn from the plant kingdom. The utilization of these natural compounds (secondary metabolites) for human aliments as well as animals begins from time immemorial. In the present paper six plants (Achyranthes aspera, Acorus calamus, Curcuma zedoria, Eruca sativa, Verbascum thapsus and Vitex negundo) are viewed for their chemical constituents, medicinal and antioxidant property. Free radicals or reactive oxygen species induce damage mainly to bio-membranes and DNA due to peroxidation mechanism, which ultimately leads to tissue damage resulting in a number of degenerative diseases. Antioxidants have been reported to prevent oxidative damage caused by free radicals and may prevent the body from various disorders. In recent years, the search for effective and more reliable non-toxic natural compounds with antioxidant activity has been intensified. The present review undertakes a brief account of research report on plants with antioxidant potential.